The Influence of Cognitive Dissonance Bias, Overconfidence Bias, and Herding Bias on the Investment Decisions of West Kalimantan Society in the Indonesia Stock Exchange - Pebriyanti; Dedi Hariyanto; Heni Safitri (www.amertainstitute.com, 2025)
This study examines the influence of cognitive dissonance bias, overconfidence bias, and herding bias on investment decisions in stocks listed on the Indonesia Stock Exchange. The study employs a questionnaire method as a data collection technique, involving a sample of 150 respondents, all of whom are residents of West Kalimantan who invest in stocks on the Indonesia Stock Exchange. The data analysis techniques used include multiple linear regression analysis, multiple correlation coefficient (R), coefficient of determination (R²), simultaneous test (F-test), and partial test (t-test). The results of the study indicate that cognitive dissonance bias, overconfidence bias, and herding bias have a positive and significant influence on investment decisions. This suggests that these three types of behavioral biases play an important role in the individual investment decision-making process. In other words, when investors experience a mismatch between their beliefs and new information, exhibit excessive self-confidence, or tend to follow the decisions of the majority, they are more likely to make investment decisions without thoroughly considering rational analysis. These findings highlight the importance of understanding investor psychology and financial literacy in minimizing the impact of cognitive biases. Proper education and enhanced awareness of financial behavior are expected to help investors make more objective and rational decisions, thereby reducing potential losses and improving the quality of investment decisions in the capital market.